MOTIVATION IN SPORT PSYCHOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Motivation is an internal energy force that determines all aspects of our behaviour; it also impacts on how we think, feel and interact with others. In sport, high motivation is widely accepted as an essential prerequisite in getting athletes to fulfil their potential. However, given its inherently abstract nature, it is a force that is often difficult to exploit fully. Some coaches, like Portugal manager Luiz Felipe ‘Big Phil’ Scolari, appear to have a ‘magic touch’, being able to get a great deal more out of a team than the sum of its individual parts; others find motivation to be an elusive concept they are forever struggling to master. What is it that makes individuals like the 45-year-old sprinter Merlene Ottey, who competed in her seventh Olympics in Athens 2004, churn out outstanding performances year in, year out? Elite athletes such as Ottey have developed an ability to channel their energies extremely effectively. Indeed, motivation is essentially about the direction of effort over a prolonged period of time. There are numerous approaches to the study of motivation. Some are based on schedules of positive and negative reinforcement (eg BF Skinner’s and Ivan Pavlov’s behaviourism) while others focus on an individual’s sense of mastery over a set of circumstances (eg Albert Bandura’s self-efficacy theory). This article explores the constituents of motivation using a contemporary approach, popularised by Americans Edward Deci and Richard Ryan, known as self-determination theory, which emphasises the role of individual choice.